Comparison of the effectiveness of 4% sodium fluoride and low-power LASER in the treatment of cervical dentin hypersensitivity (Research, Society and Development, 2020)
Objective: Evaluated the efficacy of 4% sodium fluoride solution for the treatment of DH, comparing it to low power LASER therapy. Methodology: A randomized controlled clinical trial was carried out, consisting of a test group (47 teeth) and a control group (47 teeth). For the test group, 4% sodium fluoride was applied, and the control group received low-power LASER irradiation. The therapies of the two groups were carried out in three sessions with an interval of one week between them. Before the treatment (T0), immediately after the application of therapies in each session (T1, T2 and T3), and at the times of 1 (T4), 3 (T5) and 6 (T6) months, the dental elements were submitted to the tactile and thermo-evaporative stimuli and responses were obtained using the Visual Numeric Scale (VNS). The statistical analysis of the data was performed using the non-parametric Wilcoxon, Friedman and Mann-Whitney tests. Results: In T6, the mean pain of the test group went from 5.93 to 1.73 (p